Pool boiling CHF enhancement using a honeycomb porous plate and nanofluid - Mori, Shoji; Mt Aznam, Suazlan (2019)
A honeycomb-structured ceramic porous plate (HPP) was used to increase the critical heat flux (CHF) in a saturated pool boiling. Combining the HPP with a nanofluid significantly improved the CHF compared to that obtained from a plain surface in pure water, to a maximum of approximately 3.2 MW/m2. In this paper, the mechanism for the CHF enhancement was considered by measuring the temperature of the heated surface using an ITO heater and a high-speed infrared camera. As a result, the following conclusions can be made based on our data. The average temperatures at the intersecting parts of the HPP were relatively high (more than 200 °C) compared to other locations. And when the HPP was installed on the heated surface in conjunction with the nanofluid, the wall temperatures obtained under burnout conditions decreased in the order of the intersection of an HPP wall > an HPP wall between intersections > the cell. However, dryout was initiated in the cell when burnout occurred. This result implies that further CHF improvements could be achieved if the initiation of dryout at the cell can be suppressed.